Impact of Different Sugar Syrups on the Development of the Fat Body in Worker Bees (Apis mellifera macedonica) - Svilen B. Lazarov; Petya M. Veleva; Atanas Z. Atanasov; Ivaylo S. Hristakov; Zlatko Puškadija (Agriculture)
Global climate change, intensive agriculture, and anthropogenic pollution adversely affect flowering plants and the vitality of bee colonies. In nutritional stress conditions, bees deplete the food reserves of their fat body to sustain colony life. Beekeepers play a critical role by providing supplemental nutrient solutions. This study examines the effects of various sugar syrups on the fat body development of worker bees (Apis mellifera macedonica). The colonies were divided into one control group and five experimental groups: one fed with 1:1 sugar/water syrup, one with 2:1 sugar/water syrup, one with inverted syrup (Apiinvert), one with HFCS (high-fructose corn syrup) (Isosweet), and one with 1:1 honey/water syrup. Fat body development was assessed through meticulous dissection, and the degrees of development were documented using a USB digital microscope (Bresser). The results indicate significant seasonal variations in fat body development, with winter depletion and recovery influenced by supplemental feeding. Apiinvert and honey/water syrup promoted higher fat body stages, while Isosweet led to elevated fifth degrees of development but raised concerns about potential toxicity due to the hydroxymethylfurfural (HMF) formation of improperly stored syrups. This study concludes that adequate supplemental feeding with easily digestible sugars is critical for promoting fat body development, enhancing winter survival, and ensuring overall colony health. These findings provide practical guidance for beekeepers to optimize feeding strategies and support resilient bee colonies.